The importance of the supervising professor in the Supervised Internship in Geography during the Covid-19 pandemic (Élisée - Revista de Geografia da UEG, 2023)
The objective of this text is to discuss the role of the teacher supervisor of the basic school in the monitoring of the Supervised Curricular Internship in Geography. This professional works as a co-formator in the career of undergraduate students, together with the teacher guiding the discipline at the university, and actively participates in the development of the teaching experiences that involve this academic activity. Thus, we will address the training process in the discipline of Supervised Internship in Geography III, of the seventh phase of the course of Geography of the State University of Santa Catarina (UDESC), during the first semester of 2021. The internship activities involved the figure of the supervising teacher in the elementary school, the interns and the supervising teacher. This period was marked by the COVID-19 pandemic and classes at the school took place in hybrid format, while at the university they were held exclusively in non-presence format. The research was developed from the internship reports presented by the licensees, the experiences of the professors (advisor and supervisor) and bibliographies referring to the topics addressed. Through data analysis, we consider that the supervising professor plays an ethical role in the teacher training of undergraduate students by enabling the initiation of undergraduate students in teaching and by sharing their practices and experiences in the classroom.
Keywords: Supervised Curricular Internship. Teacher Training. Geography. Supervising Professor. Teaching Ethics.